SKRINING HIPERGLIKEMIA DAN PELATIHAN MANAJEMEN DIRI PENGENDALIAN GULA DARAH PADA DIABETES MELITUS - Herwana, Elly; Yenny, Yenny; Kurniasari, Kurniasari; Kalumpiu, Joice Viladelvia; Alvina, Alvina; Soesanto, Sheila; Graciela, Audria (Jurnal Pengabdian Masyarakat Trimedika, 2025)
Diabetes mellitus (DM) is a chronic disease with a high prevalence throughout the world. Chronic hyperglycemia in DM increases the risk of complications in kidney function disorders, stroke, heart diseases, and retinopathy, which will impact to a high economic burden and decrease the quality of life in DM patients. Early detection of DM, optimal management by administering antidiabetic drugs and continuous self-management of blood sugar control will reduce the risk of DM complications. This activity was carried out with the aim of early detection of DM and to increase knowledge about DM, self-management, controlling hyperglycemia, and the risk of DM complications. Early detection screening for DM was carried out by measuring the respondent's blood sugar levels in the morning. Increasing knowledge about DM is carried out through training, counseling and interactive questions and answers with respondents. Screening for blood sugar levels found that 8 respondents (26.7%) suffered from DM. The distribution of body mass index (BMI), systolic, and diastolic blood pressure did not show significant differences between DM and non-DM respondents. Training and counseling about DM had the impact of increasing the level of respondent’s knowledge by 13.4% (83.3% vs 96.7%) so this training is expected to be useful in reducing the risk of complications for DM patients